Two Rooted Maxillary Lateral Incisor: A Case Report - singh matta, mandeep (Iranian Endodontic Journal, 2012)
An accurate diagnosis of the morphology of the root canal system is a pre-requisite for successful root canal treatment. Frequently, root canals are left untreated because the clinicians fail to identify their presence, particularly in teeth that have anatomical variations or additional root canals. In this report a maxillary lateral incisor with two roots has been described.